Glucose metabolism in pregnant women with a family history of diabetes or a history of obstetric pathology and its impact on the fetus - Saona Figari, Arturo (2015)
The study is a retrosperctivo analysis of 483 medical records of patients seen by the author in the San Felipe, Lima Clinic; in all casom test it has been practiced oral glucose tolerance because there is a family history of diabetes or a history of obstetric pathology. Of the total, 358 were pregnant and 125 were gynecological patients.